Exploring the Accessibility Legal Landscape: Accessibility requirements in mobile applications according to ABNT NBR 17060 - Da Costa Nunes, Erik Henrique; Monteiro, Ingrid Teixeira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
A good digital product often arises from a proper characterization of requirements. This reduces business risks, minimizing costs associated with rework or user rejection of the product. Accessibility is commonly regarded as a non-functional requirement, sometimes linked to usability, in order to ensure quality in the system. At least in the Brazilian context, acessibility has not being considered mandatory in industry settings. This work aims to investigate the change proposed by "ABNT NBR 17060 - Accessibility in Mobile Apps - Requirements" published in 2022, with the purpose of repositioning accessibility as a legal requirement. This study utilizes legal hermeneutics to understand how this standard reaches citizens, determining by whom, when, and what the standard must be complied with. In an effort to translate accessibility as a legal aspect into software requirements, in this paper, we report how "User Stories" may be employed to properly position this new type of requirement from the perspective of compliance.